THE IMPACT OF FINANCIAL PERFORMANCE, FIRM SIZE AND CAPITAL STRUCTURE ON FIRM VALUE - Suyanto, Suyanto; Bilang, Chintya N (JURNAL AKUNTANSI FINANCIAL STIE SULTAN AGUNG, 2023)
This study aims to prove the effect of financial performance, company size and capital structure on firm value. The sample in the study was 144 manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period. The research sample was obtained by purposive sampling technique. The analytical method used is multiple linear regression analysis using SPSS version 23. The results of this research prove that financial performance has a positive effect on firm value, firm size has a positive effect on firm value and capital structure simultaneously has a positive effect on firm value.Keywords: Financial performance, company size, capital structure, firm valueÂ